Analisis Teori Perkembangan Kognitif Jean Piaget dalam Bimbingan Belajar Anak Usia Dini - Torang Siregar (Jurnal Ilmiah Al-Muttaqin, 2025)
Cognitive development in early childhood is a crucial aspect that determines the success of learning processes in later stages. However, in practice, tutoring for young children often employs instructional approaches that are not aligned with their developmental characteristics, such as overly abstract methods and teacher-centered instruction. This condition highlights the need for a strong theoretical foundation in designing appropriate tutoring strategies for early childhood learners. Therefore, this study aims to analyze the cognitive development theory proposed by Jean Piaget and examine its relevance in early childhood tutoring. This study employs a qualitative approach using a library research method. Data sources were obtained from various original works directly related to Piaget’s cognitive development theory, such as his books and scholarly writings. Data were collected through documentation techniques and analyzed using content analysis. The findings indicate that Piaget’s cognitive development theory emphasizes stages of cognitive growth, namely sensorimotor, preoperational, concrete operational, and formal operational stages. Early childhood learners are in the preoperational stage, characterized by symbolic thinking, language development, and imagination, although still limited in logical reasoning. Key principles such as assimilation, accommodation, and constructivism form the foundation for understanding children’s learning processes. In the context of tutoring, Piaget’s theory is highly relevant, particularly in promoting experiential learning, the use of concrete materials, and play-based activities. The implications of this theory highlight the importance of designing tutoring strategies that align with children’s cognitive developmental stages to enhance effective and meaningful learning experiences. In conclusion, Piaget’s cognitive development theory provides an essential theoretical foundation for designing and developing early childhood tutoring practices that optimize children’s cognitive development.